ANALISIS DETERMINAN VOLUNTARY GRAPHICS DISCLOSURE PADA PEMERINTAH DAERAH PROVINSI DI INDONESIA - Santi Agustianti; Verawaty Verawaty (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2020)
Voluntary Graphics Disclosure (VGD) is a voluntary disclosure of public sector accounting using graphics. This method minimizes the time to analyze related information with more effective presentation quality of reports on local government finances. This study was aimed to analyze the determinants of VGD. Those are the performance, the size, the wealth, the level of dependence, and the location of local government, the age and the educational background of regional heads, audit findings and the age of local government as the characteristic of local government. The study used quantitative analysis techniques with multivariate regression. The object of this research was the provincial government in Indonesia in 2015-2017. Based on the results of hypothesis testing, performance, size, location of local government and the age of regional heads did not significantly influence VGD. Hypothesis test results showed that regional head education background and the age of the regional government had significant negative effects on VGD. However, the results of the wealth, the level of dependence and audit findings had significant positive effects on VGD. The implication of this study is for regulators in this case government accounting standards to consider the use of graphics in the disclosure of information in local government financial statements (LKPD).